Ethno-Project-Based Learning as a Community-Based Education Model for Preserving the Cultural Heritage - Widyaswari, Monica; Qodriyati, Tri 'Ulya; Mustakim; Susanto, Shobri Firman; Perez, Liann Camille Davalos (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2026)
Cultural heritage plays a strategic role in shaping local identity and strengthening learners’ character. The Ethno-Project-Based Learning model is a project-based instructional approach that integrates local cultural values as sources of learning, innovation, and skill development. This study aims to examine the implementation of this model within a learning community that collaborates with cultural figures and the local society, focusing on the transmission of Topeng Malangan culture as part of the local wisdom of the Greater Malang region. This research adopts a qualitative case study approach. Participants include cultural practitioners, community members, and learners from various age groups. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings indicate that: (a) Ethno-Project-Based Learning is implemented through culturally grounded projects such as mask-making, traditional dance, and folklore storytelling, enabling contextual and experience-based learning; (b) learner engagement emerges through intergenerational collaboration, where cultural figures, facilitators, and youth interact as co-learners; and (c) the internalization of cultural values, such as responsibility, solidarity, and cultural ethics—is reflected in learners’ participation, attitudes, and creative outputs during the learning process. These findings suggest that the model contributes to the transmission of cultural heritage by fostering active participation, meaningful engagement, and the internalization of value within the learning community. In this context, Topeng Malangan serves not only as a subject of study but also as a medium for character formation through the appreciation of embedded moral and cultural values. Keywords: ethno-project-based learning, community education, cultural heritage, cultural preservation